Risk profile, quality of life and care of patients with moderate and advanced CKD: The French CKD-REIN Cohort Study. Issue 2 (9th April 2018) - Stengel, Bénédicte; Metzger, Marie; Combe, Christian; Jacquelinet, Christian; Briançon, Serge; Ayav, Carole; Fouque, Denis; Laville, Maurice; Frimat, Luc; Pascal, Christophe; Herpe, Yves-Edouard; Morel, Pascal; et al.
Abstract: Background: The French Chronic Kidney Disease–Renal Epidemiology and Information Network (CKD-REIN) cohort study was designed to investigate the determinants of prognosis and care of patients referred to nephrologists with moderate and advanced chronic kidney disease (CKD). We examined their baseline risk profile and experience. Methods: We collected bioclinical and patient-reported information from 3033 outpatients with CKD and estimated glomerular filtration rates (eGFRs) of 15–60 mL/min/1.73 m 2 treated at 40 nationally representative public and private facilities. Results: The patients' median age was 69 (60–76) years, 65% were men, their mean eGFR was 33 mL/min/1.73 m 2, 43% had diabetes, 24% had a history of acute kidney injury (AKI) and 57% had uncontrolled blood pressure (BP; >140/90 mmHg). Men had worse risk profiles than women and were more likely to be past or current smokers (73% versus 34%) and have cardiovascular disease (59% versus 42%), albuminuria >30 mg/mmol (or proteinuria > 50) (40% versus 30%) (all P < 0.001) and a higher median risk of end-stage renal disease within 5 years, predicted by the kidney failure risk equation 12% [interquartile range (IQR) 3–37%] versus 9% [3–31%], P = 0.008. During the previous year, 60% of patients reported one-to-two nephrologist visits and four or more general practitioner visits; only 25% saw a dietician and 75% were prescribed five or more medications daily. Physical and mental quality of life (QoL) were poor, with scores <50/100. Conclusions: The CKD-REIN study highlights high-risk profiles of cohort members and identifies several priorities, including improving BP control and dietary counselling and increasing doctors' awareness of AKI, polypharmacy and QoL. Trial registration: ClinicalTrials.gov identifier: NCT03381950